Two conifer species native to Patagonia threatened by Phytophthora austrocedri. Issue 2 (21st January 2019) - Taccari, Leonardo E.; Greslebin, Alina G.; Salgado Salomón, María E.; Vélez, María L.
Abstract: Phytophthora austrocedri is a pathogen of Austrocedrus chilensis causing "Mal del Ciprés" (cypress sickness) in Patagonia and killing Juniperus communis in Britain, along with other species in the Cupressaceae. The evident association of the pathogen with members of the Cupressaceae makes it necessary to study the susceptibility of other species related to A. chilensis to prevent the emergence of new diseases. The present study tested the pathogenicity of P. austrocedri to three native and endemic conifers in South America: Fitzroya cupressoides, Pilgerodendron uviferum and Araucaria araucana . The results showed that F. cupressoides and P. uviferum were highly susceptible to P. austrocedri . Since these are endangered tree species, the outcome of this study is crucial for governmental agencies, policymakers and stakeholders.